Sirtuins and SIRT6 in carcinogenesis and in diet - de Céu Teixeira, Maria (2019)
Sirtuins are a highly conserved family of nicotinamide adenine dinucleotide (NAD)-dependent protein lysine modifying enzymes. They are key regulators for a wide variety of cellular and physiological processes such as cell proliferation, differentiation, DNA damage and stress response, genome stability, cell survival, metabolism, energy homeostasis, organ development and aging. Aging is one of the major risk factors of cancer, as many of the physiological mechanisms and pathologies associated with the aging process also contribute to tumor initiation, growth and/or metastasis. This review focuses on one the mammalian sirtuins, SIRT6, which has emerged as an important regulator of longevity and appears to have multiple biochemical functions that interfere with tumor development and may be useful in cancer prevention and for site-specific treatment. The recent evidence of the role of SIRT6 in carcinogenesis is also discussed, focusing on the potential use of SIRT6 modulators in cancer nanomedicine.